The role of student-teacher relationship in the link between social competence and involvement in bullying in the 1st grade - Visvaldas Legkauskas; Šarūnė Magelinskaitė-Legkauskienė; Albina Kepalaitė (Social Welfare: Interdisciplinary Approach)
The present study was aimed at investigating whether student-teacher relationship plays a role in the link between social competence and involvement in bullying in the 1st grade. Subjects were 408 Lithuanian 1st graders, 225 girls and 183 boys. Analysis of results using structural equation modeling releaved that bullying behavior was directly predicted by learning-related social competence, while interpersonal social competence was linked to bullying behavior via student-teacher closeness. Bullying victimization was linked to learning-related social competence via student-teacher relationship conflict.